Attenuation length of high energy neutrons through a thick concrete shield measured by activation detectors at CHARM. Issue 9 (1st September 2020) - Nakao, Noriaki; Sanami, Toshiya; Kajimoto, Tsuyoshi; Iliopoulou, Elpida; Froeschl, Robert; Brugger, Markus; Roesler, Stefan; Infantino, Angelo
ABSTRACT: A deep-penetration shielding experiment was performed at the CERN High-energy AcceleRator Mixed-field (CHARM) facility. The protons (24 GeV/c) were injected into a 50-cm-thick copper target and the released neutrons were transmitted through a bulk concrete shield located vertically upward from the target, where they were measured with bismuth and aluminum activation detectors placed at various penetration distances in the shield. From the radionuclide production rate in the activation detectors, the attenuation profiles through the concrete shield were obtained for the reactions of 209 Bi(n, x n) 210- x Bi( x = 4–9) and 27 Al(n, α) 24 Na. The attenuation length of the high-energy neutrons through ordinary concrete was estimated as 120 g/cm 2, in good agreement with Monte Carlo simulations using simple slabs as a universal geometry implemented in Particle and Heavy Ion Transport System (PHITS) code. Proton energy dependence of attenuation length was also investigated with simulations by PHITS code and comparisons with the published data were discussed.